The Description of Health Protocol Implementation After Covid-19 Vaccination District Workers in Kupang City - Gagi, Cicilia Angelis; Berek, Noorce Ch; Ndoen, Enjelina M (Journal of Health and Behavioral Science, 2023)
Abstract. Corona Virus Diseases 19 or COVID-19 is a global pandemic that has been established by WHO since March 11 2020. WHO data shows that globally, the total confirmed cases of COVID-19 as of January 24, 2022, were 340,543,962 cases with a total of 5,570 deaths. 163. Vaccination is one of the steps taken by the government to reduce the spread of COVID-19. Vaccination is also believed to be able to reduce the severe symptoms that will be experienced by sufferers who have contracted COVID-19. As vaccination activities continue, health protocols must also be implemented. Vaccination basically does not determine someone will automatically be free from transmission of COVID-19. The purpose of this study was to describe knowledge, attitudes, and actions regarding the implementation of health protocols after COVID-19 vaccination for workers at the Kupang City sub-district office. This type of research is quantitative with a descriptive approach. The population in this study was 113. The sample size was 89 workers. The sampling technique uses cluster sampling. The results showed that 94.4% of respondents had good knowledge, 59.6% of respondents had good attitudes, and 41.6% of respondents had good actions. The application of health protocols must still be carried out even though vaccinations have been carried out, because vaccination will not always make someone free from COVID-19 but will help prevent it. Keywords: COVID-19, Distric Workers, Vaccination